Jurisdiction Of Charity Tradition In Strengthening The Generous Character Of Students Of TPQ Daarul Hamdi Ulujami Jakarta Selatan - Muhajir, Achmad; Kurnia, Rina (Sinergi International Journal of Islamic Studies, 2023)
As social beings, humans in living life will definitely depend on other humans. Therefore, religion provides teachings to spread love between people, one of which is by giving alms as a form of reflection to create love between people. And to make a person who likes to give or someone who has the character of a donor requires habituation from an early age, because in terms of the character of Helen G. D. it gives an understanding that character is not inherited, but something that is built continuously day by day through thoughts and actions, thoughts for the sake of thought, action after action. As was carried out by TPQ Daarul Hamdi Ulujami South Jakarta, namely Friday charity activities for students every Friday as a reflection of the teachings of the prophet's hadith. it is hoped that students will have high social sensitivity so as to produce philanthropic characters. This research uses descriptive qualitative method. The purpose of this research is to cultivate characters that are in accordance with the values of Islamic teachings.